Respon beberapa varietas Kedelai (Glycine max L. Merr) terhadap tingkat salinitas air penyiraman - Sheila Rahma Yunita; Sutarno Sutarno; Eny Fuskhah (Journal of Agro Complex, 2018)
The objective of this research was to study the hardiness of several soybean varieties to different levels of salinity water and to find out  the effect of salinity on soybean growth and production. This research was conducted in Greenhouse and Laboratory of Ecology and Plant Production at Faculty of Animal and Agricultural Sciences, Diponegoro University from February to May 2017. The research was arranged using completely randomized factorial design with the first factor was soybean varieties (Dering 1, Demas 2, and Devon 3) and the second factor was water salinity level (0 dS/m, 3 dS/m, 6 dS/m and  9 dS/m). The result showed that the treatment of 3 dS/m water salinity level did not affect at plant height and number of leaves until 4th week. However salinity of 6 and 9 dS/m decreased the height and number of leaves from all varieties. Salinity level of 3, 6 and 9 dS/m decreased the number of pod, weight of pod and 100 seeds weight from all verieties. Dering 1 yielded 100 seeds weight heavier than Demas 1 and Devon 1.Keywords : growth, production, salinity, soybean.